The Inventory of Geological Heritage of the State of So Paulo, Brazil: Methodological Basis, Results and Perspectives - Motta Garcia, Maria da Gloria; Brilha, Jose; Lima, Flavia Fernanda de; Vargas, Jean Carlos; Perez-Aguilar, Annabel; Alves, Adriana; Cruz Campanha, Ginaldo Ademar da; Duleba, Wania; Faleiros, Frederico Meira; Fernandes, Luiz Alberto; Matos Fierz, Marisa de Souto; Garcia, Maria Judite; et al. (Springer, 2018)
An inventory of geological sites based on solid and clear criteria is a first step for any geoconservation strategy. This paper describes the method used in the geoheritage inventory of the State of So Paulo, Brazil, and presents its main results. This inventory developed by the geoscientific community aimed to identify geosites with scientific value in the whole state, using a systematic approach. All 142 geosites representative of 11 geological frameworks were characterised and quantitatively evaluated according to their scientific value and risk of degradation, in order to establish priorities for their future management. An online database of the inventory is under construction, which will be available to be easily consulted and updated by the geoscientific community. All data were made available to the State Geological Institute as the backbone for the implementation of a future state geoconservation strategy.
Keywords: Geoheritage; Geosite; Inventory; Brazil